Sexuality (Gender) and its Impact on Family Cohesion in Iraq:Visions of the Role of official State Institutions - Ismail, Prof. Dr. Wael Muhammad (Journal of Legal and Political Studies, 2018)
The Sexuality or gender as it is clear to the reader has two meanings or the first negative signifies the lack of equality between men and women is the work on the sexual differentiation between men and women according to social and genetic and moral structures and differences, and the second positive for what is supposed to be assumed to be gender equality between men and women, however It seems that the positive meaning may also show the negative objective of the claims or demands of equality, which is carried out by Islamic organizations and feminist movements Islamic feminists Islamic and Islamic and other strange terms that have touched the doors of all countries World, including Arab societies. The concept of gender is that the differences between males and females are based primarily on social rather than biological criteria, meaning that societies determine the expected roles of Adam and Eve. But the problem arises when some advocates of gender equality seek to abolish or marginalize differences between males and females without taking into account many religious, ethical, logical and realistic considerations, which may affect societies with patriarchal and tribal traditions, including Iraq. and the repercussions of globalization will be more violent and more, especially if these goals merged with the political dimensions of the dismantling of the Iraqi family basis of the foundation of society and citizenship in Iraq, hence the need to confront the constitutional and legislative phenomenon of women aimed at mixing poison with honey.
Keywords: Gender equality; Genetic; biological criteria; Islamic feminists